2005
DOI: 10.1152/ajplung.00250.2004
|View full text |Cite
|
Sign up to set email alerts
|

The murine SP-C promoter directs type II cell-specific expression in transgenic mice

Abstract: . The murine SP-C promoter directs type II cell-specific expression in transgenic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In addition, the inclusion of proximal sequences for the regulation of gene expression within the BAC construct decreases the possibility of nonspecific expression of GFP. Previous studies in transgenic lines with a murine SPC promoter provided a plausible explanation that species differences, including their chromatin environments, may account for the aberrant bronchiolar expression obtained from the human SPC promoter, rather than position effects or the copy number of transgenes (30,32). Finally, a GFP 1 cell in SPC H2B-GFP mice may no longer be expressing SPC, but rather its precursor cell expressed SPC, and GFP is simply observed before protein decay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the inclusion of proximal sequences for the regulation of gene expression within the BAC construct decreases the possibility of nonspecific expression of GFP. Previous studies in transgenic lines with a murine SPC promoter provided a plausible explanation that species differences, including their chromatin environments, may account for the aberrant bronchiolar expression obtained from the human SPC promoter, rather than position effects or the copy number of transgenes (30,32). Finally, a GFP 1 cell in SPC H2B-GFP mice may no longer be expressing SPC, but rather its precursor cell expressed SPC, and GFP is simply observed before protein decay.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also demonstrated the importance of species-specific promoter use for proper AT2 cell expression (30,31). Further detailed analysis of the murine SPC gene promoter revealed the particular sequences needed for (Received in original form November 22, 2011 and in final form October 19, 2012) AT2 cell-specific expression (32). More recently, the creation of SPC-reverse tetracycline transactivator (rtTA) and SPC-Cre knock-in mice that are useful for analyzing AT2 cells in vivo has also been reported (8,21).…”
mentioning
confidence: 96%
“…(25). The SP-C gene promoter also has been shown to be specific for type II cells (12). Our results demonstrate that different ECM molecules and integrin subunits differentially mediate the effects of mechanical strain on fetal type II lung epithelial cell differentiation.…”
Section: Discussionmentioning
confidence: 59%
“…The relative positions of the upstream SFTPC mutations at -1167bp, -1647bp, and -2385bp overlap with a conserved region between the mouse and human promoters. Deletion analysis of the SFTPC promoter in transgenic mice and stabletransfected mouse lung epithelial cells demonstrated that this region encodes a transcriptional enhancer that requires a chromatin context for full activity [33,34]. These findings suggest that mutations in SFTPC regulatory elements may decrease expression and account for disease similar to mutations within the SFTPC gene structure that reduce expression or processing.…”
Section: Surfactant Protein C (Sp-c) Abnormalities Are Associated Witmentioning
confidence: 92%